Flurbiprofen inhibits heme induced NLRP3 inflammasome in Berkeley sickle cell disease mice - Kour, Dilpreet; Ali, Mehboob; Khajuria, Parul; Sharma, Kuhu; Ghosh, Palash; Kaur, Sukhleen; Mahajan, Surbhi; Ramajayan, P.; Bharate, Sonali S.; Bhardwaj, Subhash; Sawant, Sanghapal D.; Reddy, D. Srinivasa; et al. (Frontiers in Pharmacology, 2023)
Sickle cell disease (SCD) is accompanied by several complications, which emanate from the sickling of erythrocytes due to a point mutation in the β-globin chain of hemoglobin. Sickled erythrocytes are unable to move smoothly through small blood capillaries and therefore, cause vaso occlusion and severe pain. Apart from pain, continuous lysis of fragile sickled erythrocytes leads to the release of heme, which is a strong activator of the NLRP3 inflammasome, thus producing chronic inflammation in SCD. In this study, we identified flurbiprofen among other COX-2 inhibitors to be a potent inhibitor of heme-induced NLRP3 inflammasome. We found that apart from being a nociceptive agent, flurbiprofen exerts a strong anti-inflammatory effect by suppressing NF-κB signaling, which was evidenced by reduced levels of TNF-α and IL-6 in wild-type and sickle cell disease Berkeley mice models. Our data further demonstrated the protective effect of flurbiprofen on the liver, lungs, and spleen in Berkeley mice. The current SCD pain management regime relies mainly on opiate drugs, which is accompanied by several side effects without modifying the SCD-related pathology. Considering the potent role of flurbiprofen in inhibiting NLRP3 inflammasome and other inflammatory cytokines in SCD, our data suggests that it can be explored further for better SCD pain management along with the possibility of disease modification.